Lineage switch from acute lympheal leukemia (ALL) to acute myeloid leukemia (AML): Report of a case - Zatta-Cóndor, Julio (2020)
Introduction: Acute Lymphatic Leukemia (ALL) represents the most frequent pediatric malignant disease, representing at least 25% of childhood cancer cases. Lineage switch from Acute Lymphatic Leukemia to Acute Myeloid Leukemia (AML) represents approximately 6 to 9% of recurrent cases, and is observed more frequently in children. Case report: a 9-year-old male patient with an Initial Diagnosis of Very High Risk ALL-B, relapses with AML after 1 year 9 months of receiving treatment with chemotherapy and prophylactic radiotherapy. Conclusion: There are different mechanisms that could explain the Lineage switch between acute lymphocytic leukemia to acute myeloid leukemia; in our patient we could talk about possible factors that influenced the Lineage switch: bipolar progenitors, clonal selection, chemotherapy.